Comprehensive understanding of smart product service system from multi-dimension and multi-perspective: An innovative service model for Customer-product Interaction Life Cycle (CILC). (April 2022) - Zhang, Xianyu; Ming, Xinguo
Highlights: An innovative service model for CILC is constructed. A smart product service system for CILC is proposed. A service impact factors analysis method for CILC is proposed. It has a certain reference value for industry and government. Abstract: With the improvement of living standards and the rapid development of the Internet, customers gradually pursue personalized smart products and services. Traditional smart product service system is mainly aimed at the service of customers and products in one or several interactive links. Furthermore, in the mass personalization model, in order to give full play to the customer experience and participation satisfaction, it is necessary to study the smart product service system based on the interaction between customers and products. However, there is a gap in the research on integrating the whole life cycle of customer-product interaction. In order to meet this industrial need, the innovation of this paper is to construct an innovative service model for Customer-product Interaction Life Cycle (CILC) and analyse the service impact factors and countermeasures using fuzzy DEMATEL method. The study can provide enterprises with the top-level framework and decision-making of smart product service system based on CILC, and realize the effective integration, expansion and value-added of service resources. At the same time, the application of this research methods can shorten the distance between customers and products, improve customer satisfaction.